Are We Over-Treating Insect Bite Related Periorbital Cellulitis in Children? The Experience of a Large, Tertiary Care Pediatric Hospital. (January 2019) - Friedel, Nadav; Scolnik, Dennis; Rimon, Ayelet; Orbach, Rotem; Laat, Sharon; Glatstein, Miguel M.
Abstract : Introduction: Preseptal (periorbital) and orbital cellulitis are potentially catastrophic infections near the eye. Preseptal cellulitis is far more common, and although classically reported to be associated with dacrocystitis, sinusitis/upper respiratory infection, trauma/surgery, or infection from contiguous areas, it can also be associated with insect bites. The objective of this study was to determine the prevalence of insect bite-associated preseptal cellulitis and to compare clinical findings and outcomes of these patients with those having other causes for the condition. Methods: Retrospective chart review of children with a final discharge diagnosis of periorbital cellulitis from January 2009 to December 2014 at a tertiary care children' hospital. Results: 213 children were diagnosed with preseptal cellulitis during the 5-year study period, of whom 60 (28%) were associated with insect bites. Patients in the noninsect bite group more commonly had fever at presentation ( P < 0.001), with increased white blood cell and C reactive protein values (both P < 0.001). No patient with insect bite-associated preseptal cellulitis presented with fever, and none underwent radiographic testing or computerized tomography; their mean age was also lower ( P < 0.001) and length of stay was significantly shorter. Conclusions: This study suggests that children with preseptal cellulitis associated with insect bites could be candidates for oral antibiotic therapy with outpatient follow-up by.